Reflections on employment relations at a time of the COVID-19 pandemic (Research, Society and Development, 2021)
The pandemic originated from COVID-19 brought to Brazilian law several challenges, especially in relation to labor law, needing to adapt to the "new normal" where the working day is shorter, consequently generating lower wages and affecting the economy. unemployment due to restrictive measures taken by the Union, States and Municipalities, establishing the need to guarantee a source of income for the part of the population that does not have a job and the need to maintain the jobs that were maintained through social policies. The understanding of how labor law was impacted during this period is the main objective of this study, and how the State managed to deal and try to guarantee the economically active population ways to circumvent these storms, using the bibliography for the analysis of the phenomenon, through a bibliographical research with a qualitative approach, mainly in relation to doctrine and laws and decrees sanctioned in the period, thus making use of the inductive method to reach the result that laws and decrees were responsible for impacting and changing labor laws, in addition to ensuring welfare benefits the population in a vulnerable situation.